Predictive value of red cell distribution width to albumin ratio for acute kidney injury in patients with acute pancreatitis - Jin Zhao; Yuan Peng; Chenyang Xu (PLoS ONE, 2026)
Background Red blood cell volume distribution width (RDW) and albumin have been increasingly recognized for their roles in inflammatory diseases. However, the relationship between RDW-to-albumin ratio (RAR) and acute kidney injury (AKI) in acute pancreatitis (AP) patients has not been clarified. Therefore, the research aims to explore the correlation between RAR and AKI risk in critically ill patients with AP. Methods Patients diagnosed with AP from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database were included in this retrospective study. The primary outcome measure was the incidence of AKI. Logistic regression analysis and restricted cubic spline were used to evaluate the relationship between RAR and AKI incidence in AP patients. Subgroup analyses were used to test interactions. Results In total, 600 patients were enrolled in the study. The incidence of AKI was 77.3%. Based on multiple logistic regression analysis, RAR exhibited a positive association with AKI incidence as either a continuous (OR 1.46, 95% CI 1.22–1.76, P < 0.05) or categorical variable (OR 2.79, 95% CI 1.69–4.59, P < 0.05). The restricted cubic splines model illustrated the linear relationship between higher RAR and increased risk of AKI in AP patients. Conclusions High RAR is an independent risk factor for AKI in critically ill patients with AP. Early assessment of RAR may facilitate risk stratification to guide clinical management, thereby improving clinical outcomes.